Sensitive label-free electron chemical capacitive signal transduction for D-dimer electroanalysis - Marques, Simone M. [UNESP]; Santos, Adriano [UNESP]; Gonçalves, Luís M.; Sousa, João C.; Bueno, Paulo R. [UNESP] (Elsevier, 2015)
D-dimer, an important biomarker in emergency medicine, was determined by applying a label-free electrochemical capacitive approach with an antibody-based selective biosensor consisting of an electroactive self-assembled monolayer mounted on a commercially available gold electrode. Electrochemical measurements were performed by an impedance-derived approach (based on observing the complex capacitance diagrams from where electrochemical capacitance can be obtained as transducer signal) from which it was possible to obtain low limits of detection of 50 fmol L-1 in buffer (PBS) and 7 pmol L-1 in undiluted human serum (performed without any kind of sample pre-treatment), with good coefficient of determination (r2 ≥ 0.99) in a clinically relevant D-dimer concentration range (from 1 to 1,000 ng mL-1). These electro analytical/chemistry results pave the way to the creation of low-cost and reliable point-of-care electrochemical approach for the quantitative bedside determination of D-dimer in clinical samples, thus speeding up the diagnosis of potentially lethal, nonetheless treatable, clinical conditions like pulmonary embolism.
Keywords: Biosensor; D-dimer; Electroanalysis; Electrochemical Capacitance; Pulmonary embolism; Self-assembled monolayer